2010
DOI: 10.1002/ejoc.201000787
|View full text |Cite
|
Sign up to set email alerts
|

2‐Substituted Benzo[b]furans from (E)‐1,2‐Dichlorovinyl Ethers and Organoboron Reagents: Scope and Mechanistic Investigations into the One‐Pot Suzuki Coupling/Direct Arylation

Abstract: Abstract2‐Substituted benzo[b]furans can easily be assembled from simple phenols, boronic acids or other organoboron reagents, and trichloroethylene. The overall process requires only two synthetic steps, with the key step being a one‐pot sequential Suzuki cross‐coupling/direct arylation reaction. The method tolerates many useful functional groups and does not require the installation of any other activating functionality. The modular nature of the process permits the rapid synthesis of many analogues using es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 103 publications
0
25
0
Order By: Relevance
“…The desired Wittig reagent was readily prepared from the conveniently substituted ortho ‐hydroxybenzyl alcohol Ia – Ig and PPh 3 ⋅HBr 4043. The benzofuran structures4449 were confirmed by 1 H NMR, 13 C NMR, mass spectrometry, and elemental analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The desired Wittig reagent was readily prepared from the conveniently substituted ortho ‐hydroxybenzyl alcohol Ia – Ig and PPh 3 ⋅HBr 4043. The benzofuran structures4449 were confirmed by 1 H NMR, 13 C NMR, mass spectrometry, and elemental analyses.…”
Section: Resultsmentioning
confidence: 99%
“…General procedure for the preparation of 2‐phenylbenzofuran : A mixture of 2‐hydroxybenzyltriphenylphosphonium bromide (1.10 mmol) and benzoyl chloride (1.11 mmol) in a mixed solvent (toluene 20 mL and Et 3 N 0.5 mL) was stirred under reflux for 2 h. The precipitate was removed by filtration. The filtrate was concentrated, and the residue was purified by silica gel chromatography (hexane/EtOAc 9:1) to give the desired compounds 1 – 10 4449…”
Section: Methodsmentioning
confidence: 99%
“…The first example involves an intramolecular direct arylation of an arene with a vinyl chloride to form benzofuran derivatives. [13] As shown in Scheme 2 a, the reaction of a substrate containing one deuterium in the ortho position gives rise to a k H /k D value of 4.0. Many authors have concluded from similar intramolecular competition experiments that C À H bond cleavage occurs in the rate-or turnoverlimiting step.…”
mentioning
confidence: 99%